مكانة حماية البيئة في ظل وثائق التعمير في التشريع الجزائري - طهراوي, السعيد; قوق, أم الخير (جامعة الوادي.University eloued, 2022)
هتم أدوات التهيئة والتعمير بالانشغال البيئي، ضمن السياسة العامة للتهيئة والتعمير من خلال وثائق التعمير التوقعية، المتمثلة في المخطط التوجيهي للتهيئة والتعمير الذي يهدف إلي تنظيم النشاط العمراني للمدن على مدى البعيد والقصير، بما يكفل وقاية مسبقة ضد مخاطر التعمير على المكون البيئي، أما وثائق التعمير التفصيلية المتمثلة في مخطط شغل الأراضي فدوره يكون على مستوى التطبيقي من خلال ضبط وتنظيم استعمالات المجال بما يتوافق مع التوجهات العامة لوثائق التعمير التوقعية. وللإلمام بجميع جزئيات هذا الدراسة القانونية، نسلط الضوء على مكانة التي يشغلها الاعتبار البيئي داخل وثائق التعمير المنظمة للمجال الحضري في الجزائر. :Abstract Within the general policy of planning and reconstruction, planning and reconstruction tools are concerned with the environmental issue through prospective reconstruction documents. These documents are represented in the guiding plan of planning and reconstruction that aims at regulating the urban activity in long and short terms in order to ensure a prior protection against the risks of urbanization on the environmental component. Concerning the role of detailed reconstruction documents embodied in the land use plan, it operates at practical level through controlling and regulating the use of the field with the general directions of the prospective reconstruction documents. In order to understand all the details of this judicial study, we focus on the status of the environmental consideration within the urban planning documents in Algeria.
Keywords: الانشغال البيئي، وثائق التعمير التوقعية، مكانة البيئة، تنظيم العمراني للمدن; environmental Issue , Prospective reconstruction documents, Status of Environment , Urban organization of cities.